Valorisation of natural fibres from African baobab wates by the production of activated carbons for adsorption of Diuron - Tchikuala, Emilio (2017)
In this work we report the use of a natural fibrous biomass, the African Baobab, as precursor to produce activated carbons tailored for the removal of a pollutant frequently found in water streams, the herbicide Diuron. The precursors used were Baobab wastes, namely bark, wood and seeds, collected in Angola. The activated carbons produced by physical activation with carbon dioxide showed an interesting porosity with apparent surface area and pore volume, up to 2130m2g-1 and 0.99cm3g-1, respectively. All the activated adsorbents are of microporous nature, with mean pore width between 0.69 and 1.94nm. Selected samples were tested for the adsorption of Diuron from liquid-phase. The maximum adsorption capacity reached 400mgg-1 for sample BS-62. This work shows the suitability of using Baobab wastes to produce activated carbons, which can be considered a new route to the valorization of its wastes, with good properties for the adsorption of Diuron.